Gender Nuances in Human-Computer Interaction Research - Barros De Amorim, Israel Lucas; Santos Dos Santos, Suzane; Moreira Miranda Da Silva, Ingrid; Rios Da Hora Rodrigues, Kamila; Pereira Mota, Marcelle (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Many studies are being done in the Human-Computer Interaction (HCI) area to identify gender nuances in how hardware and software are thought and built. According to bias prevention, identification, and resolution techniques, the objective is to establish an inclusive scenario. This paper presents a systematic literature review on gender and HCI, synthesizing studies where these concepts are analyzed on how HCI research discusses gender nuances, aspects, and issues. Also, to comprehend how interventions have been suggested and the frequency of those studies proposing interventions, as well as how they have been applied to diminish gender disparities in technological processes. The results indicated that the way of dealing with gender in technology has changed over the years, after including experiences of intersectional and indeterminate genders, especially considering methods submitted by academic research, where “Feminist HCI” was the most considered technique for working with gender issues, but it was mainly present from 2012 to 2021. Similarly, it was shown that most of the proposed interventions are focused on detecting gender bias in technologies, not specifically on solving them.